Review of Human Rights Theory in Philosophical and Legal Perspectives - Hendra Busriani; Asti Nurul Puspita (Program Pascasarjana UIN Sumatera Utara Medan, 2024)
Human Rights (HAM) are rights that every person possesses from birth, granted by God Almighty. They are fundamental rights that belong to every individual and should not be interfered with. However, in practice, human rights cannot be fully implemented because they must consider the public interest, the rights of others, and public order. This article examines the meaning of human rights from an etymological perspective, expert views, and legal provisions at the national and international levels. Furthermore, this article discusses the limitations of human rights, which refer to the principles of legality, proportionality, and the public interest. These concepts are drawn from the thoughts of figures such as Hobbes, Locke, Rousseau, and also the theory of utilitarianism. Therefore, restrictions on human rights are considered legitimate if the goal is to protect the rights of others and maintain balance in national and state life.